Imaging Findings in Dysgerminoma in a Case of 46 XY, Complete Gonadal Dysgenesis (Swyer syndrome) - Yadav, Pratiksha (J Clin Diagn Res, 2016)
A 46 XY pure gonadal dysgenesis also known as Swyer syndrome. These patients are phenotypic females with normal female external genitalia and absent testicular tissue. The patients with swyer syndrome have streak gonads and increased risk of dysgerminoma and gonadoblastoma. We present a case of dysgerminoma in dysgenetic gonads of swyer syndrome. A 23-year-old female had come with complaints of primary amenorrhea, pelvic mass and abdominal pain. Clinical findings, pathology investigation and imaging findings revealed swyer syndrome. On MRI it showed a large lobulated mass in the pelvis. Mass was excised and dysgerminoma was given on the histopathology.